Are variations of direct and indirect plant interactions along a climatic gradient dependent on species' strategies? An experiment on tree seedlings. Issue 5 (28th September 2015) - Defossez, Emmanuel; Courbaud, Benoît; Lasbouygues, Olivier; Schiffers, Katja; Kunstler, Georges
Abstract : Investigating how interactions among plants depend on environmental conditions is key to understand and predict plant communities' response to climate change. However, while many studies have shown how direct interactions change along climatic gradients, indirect interactions have received far less attention. In this study, we aim at contributing to a more complete understanding of how biotic interactions are modulated by climatic conditions. We investigated both direct and indirect effects of adult tree canopy and ground vegetation on seedling growth and survival in five tree species in the French Alps. To explore the effect of environmental conditions, the experiment was carried out at 10 sites along a climatic gradient closely related to temperature. While seedling growth was little affected by direct and indirect interactions, seedling survival showed significant patterns across multiple species. Ground vegetation had a strong direct competitive effect on seedling survival under warmer conditions. This effect decreased or shifted to facilitation at lower temperatures. While the confidence intervals were wider for the effect of adult canopy, it displayed the same pattern. The monitoring of micro‐environmental conditions revealed that competition by ground vegetation in warmer sites could be related to reduced water availability; and weak facilitation by adult canopy in colder sites to protection against frost. For a cold‐intolerant and shade‐tolerant species ( Fagus sylvatic a), adult canopy indirectly facilitated seedling survival by suppressing ground vegetation at high temperature sites. The other more cold tolerant species did not show this indirect effect ( Pinus uncinata, Larix decidua and Abies alba ). Our results support the widely observed pattern of stronger direct competition in more productive climates. However, for shade tolerant species, the effect of direct competition may be buffered by tree canopies reducing the competition of ground vegetation, resulting in an opposite trend for indirect interactions across the climatic gradient.